Deregulation of electricity markets: The Norwegian experience - Torstein Bye; Einar Hope (Statistics Norway, Research Department, 2005)
In this paper, we describe the approach to, and experience of, the deregulation and liberalisation of the Norwegian electricity sector from 1991. The Norwegian electricity market was subsequently integrated with the Swedish, Finnish and Danish markets to become the Nordic electricity market: the first common, integrated, intercountry electric power market in the world. We discuss the background to electricity market reform, the analytical and legal foundations for reform, and the chosen market and regulatory design. We find that the market has performed well in terms of economic efficiency and market functionality, even when exposed to severe supply shocks because of water shortages for a power system that relies heavily on hydropower. However, we also identify issues and challenges that must be addressed to improve the performance of the Nordic electricity market and its regulatory system.
Keywords: D01; D21; D41; D42; Q4; 330; Deregulation; Market design; Electricity markets